Genomic Analysis Reveals the Genetic Determinants Associated With Antibiotic Resistance in the Zoonotic Pathogen Campylobacter spp. Distributed Globally - Rivera-Mendoza, Daniel; Martínez-Flores, Irma; Santamaría, Rosa I.; Lozano, Luis; Bustamante, Víctor H.; Pérez-Morales, Deyanira (Frontiers in Microbiology, 2020)
The genus Campylobacter groups 32 Gram-negative bacteria species, several being zoonotic pathogens and a major cause of human gastroenteritis worldwide. Antibiotic resistant Campylobacter is considered by the World Health Organization as a high priority pathogen for research and development of new antibiotics. Genetic elements related to antibiotic resistance in the classical C. coli and C. jejuni species, which infect humans and livestock, have been analyzed in numerous studies, mainly focused on local geographical areas. However, the presence of these resistance determinants in other Campylobacter species, as well as in C. jejuni and C. coli strains distributed globally, remains poorly studied. In this work, we analyzed the occurrence and distribution of antibiotic resistance factors in 237 Campylobacter closed genomes available in NCBI, obtained from isolates collected worldwide, in different dates, from distinct hosts and comprising 22 Campylobacter species. Our data revealed 18 distinct genetic determinants, genes or point mutations in housekeeping genes, associated with resistance to antibiotics from aminoglycosides, -lactams, fluoroquinolones, lincosamides, macrolides, phenicols or tetracyclines classes, which are differentially distributed among the Campylobacter species tested, on chromosomes or plasmids. Three resistance determinants, the blaOXA-493 and blaOXA-576 genes, putatively related to -lactams resistance, as well as the lnu(AN2) gene, putatively related to lincosamides resistance, had not been reported in Campylobacter; thus, they represent novel determinants for antibiotic resistance in Campylobacter spp., which expands the insight on the Campylobacter resistome. Interestingly, we found that some of the genetic determinants associated with antibiotic resistance are Campylobacter species-specific; e.g., the blaOXA-493 gene and the T86V mutation in gyrA were found only in the C. lari group, whereas genes associated with aminoglycosides resistance were found only in C. jejuni and C. coli. Additional analyses revealed how are distributed the resistance and multidrug resistance Campylobacter genotypes assessed, with respect to hosts, geographical locations and collection dates. Thus, our findings further expand the knowledge on the factors that can determine or favor the antibiotic resistance in Campylobacter species distributed globally, which can be useful to choose a suitable antibiotic treatment to control the zoonotic infections by these bacteria.